Business development and eradication of illicit crops: the case of vereda Nueva Colombia department of Meta Colombia - Mendívil-González, Guillermo; González-Díaz, Jaime E.; Peroza-Daza, José D. (EFIM Ediciones, 2021)
This paper aims to identify the relationship between business development and the strategy for the eradication of illicit crops, through a proposal for the Vereda Nueva Colombia Department of Meta Colombia. This work was based on a study with a documentary design. This text is the product of a descriptive documentary design research, and finally, it is projective as it presents a proposed solution to the identified problem. The article initially makes a historical overview of the drug trafficking problem in Colombia during the second half of the 20th century, describing the links in the productive chain of the illicit drug business in the global context, to later present the evolution of public policies in the country focused on the eradication of illicit crops, consequently it presents a theoretical analysis of the business development construct, to end with a proposal for its application to the eradication of crops, which focuses on four main theme: dialogue between social institutions and creation of tissue social, state presence, improvement of road and productive infrastructure, and consolidation of productive processes, their commercialization and added value.